A Study Investigating the Association of Dermatological and Infusion Reactions to Infliximab and Infliximab Trough Levels. Issue 1 (2015) - Huang, Vivian Wai-Mei; Dhami, Neil; Fedorak, Darryl; Prosser, Connie; Shalapay, Carol; Kroeker, Karen Ivy; Halloran, Brendan Phillip; Dieleman, Levinus Albert; Fedorak, Richard Neil
Abstract : BACKGROUND: Although infliximab is an effective therapy for inflammatory bowel disease (IBD), it is associated with dermatological events and infusion reactions. It is not known whether a relationship between these adverse events (AEs) and infliximab trough levels (ITLs) exists. OBJECTIVES: To report the prevalence of infliximab-associated AEs in IBD patients receiving stable maintenance infliximab therapy, and to correlate ITLs with dermatological and infusion reactions to infliximab. METHODS: Adult IBD patients receiving stable maintenance infliximab therapy were recruited from the University of Alberta Infusion Clinic (Edmonton, Alberta). ITLs were measured in blood samples collected before infusion, and the patients' records were reviewed for dermatological and infusion reactions to infliximab. RESULTS: One-quarter (18 of 71 [25.4%]) of patients experienced dermatological or infusion reactions to infliximab: nine (12.7%) dermatological events and nine (12.7%) infusion reactions. The median ITL was similar among patients with and without these AEs (7.2 μg/mL [interquartile range (IQR) 2.0 μg/mL to 13.3 μg/mL] versus 6.6 μg/mL [IQR 3.2 μg/mL to 12.7 μg/mL]; P=0.648). The median ITL of patients who experienced infusion reactions (2.0 μg/mL [IQR 0.1 μg/mL to 5.7 μg/mL]) was lower than that of patients who experienced no such AEs (6.6 μg/mL [IQR 3.2 μg/mL to 12.7 μg/mL]; P=0.008]) and lower than that of patients who experienced dermatological AEs (13.3 μg/mL [IQR 8.8 μg/mL to 17.4 μg/mL]; P<0.001). CONCLUSION: One-quarter of IBD outpatients receiving stable maintenance infliximab therapy experienced dermatological and infusion reactions. Low ITLs were correlated with infusion reactions, and normal or high ITLs with dermatological events.